Interpretive interactionism - Denzin, Norman K. (Applied social research methods series ;, 2001)
"Interpretive Interactionism" is organized in terms of seven chapters. Chapter 1 defines the approach. Its basic assumptions and terms are given. It is compared to more traditional, quantitative social science methodology. I also compare interpretive interactionism to the "Critical Theory" of the Frankfurt School, and indicate its affinities with recent feminist thought. I locate this perspective within the sociological tradition established by C. Wright Mills (1959) in "The Sociological Imagination." Chapter 2 discusses how meaningful, biographical experience is secured. Chapter 3 outlines the interpretive process. Chapter 4 addresses how the researcher situates an interpretive study. Chapter 5 analyzes thick description, and Chapter 6 shows how interpretation is done. Chapter 7 summarizes and presents the main conclusions of this study. It emphasizes the existential nature of this research. A glossary of terms is included at the end of the book.